A Case Study on Nutritional Storage and Heat Processed Honey: Exploring the Benefits and Therapeutic Attributes of Honey (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Honey is the food derived entirely from the work of honeybees operating upon the nectar of flowers and other sweet exudation of plants.In India, the consumption of honey is mainly restricted to medicinal purposes.Honey is well known for healing of wounds and its effect on nervous system.Honey facilitates better physical performance and resistance to fatigue. Honeyis used for treating various digestive and assimilation problems. Honey alsohelps in calcium fixation in bones, cures anaemia, anorexia, insomnia andreduces fever. Honey is valued also for some of its therapeutic attributes. Itimproves the resistance of the body by improving the biological processes oforgans and systems. It facilitates proteins and fat digestion thus constitutesan excellent anti-dyspeptogenic factor (Shamala and Jyothi 1999). Honey hastonic effect. Its medicinal property neutralizes fatigue, compensatoryhypotonia, as well as the adverse effects of the other substances added whenused in the preparation of beverages (Shamala and Jyothi 1999). Honey providesimmediately available calories, for healthy and sick people. Honey consumptionbenefits digestive apparatus, respiratory system, skin and wound healing andeye disorders. Honey is also good for diabetics and to normalize kidneyfunction.